2021
DOI: 10.1016/j.eclinm.2021.100811
|View full text |Cite
|
Sign up to set email alerts
|

Impact of follow up blood cultures on outcomes of patients with community-onset gram-negative bloodstream infection

Abstract: Background: The role of follow up blood cultures (FUBC) in the management of gram-negative bloodstream infection (GN-BSI) remains controversial. This retrospective cohort study examines the association between obtaining FUBC and mortality in GN-BSI. Methods: Hospitalized adults with community-onset GN-BSI at Prisma Health-Midlands hospitals in South Carolina, USA from January 1, 2010 to June 30, 2015 were identified. Patients who died or were discharged from hospital within 72 h were excluded to minimize impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Six studies addressed only KQ1, 6 , 7 , 10 , 21 , 22 , 27 4 addressed only KQ2, 28 , 29 , 30 , 31 and 5 studies addressed both KQs. 5 , 8 , 9 , 11 , 32 Study and patient characteristics of included studies are reported in the Table . There were 8007 patients in studies that addressed KQ1 and 3243 patients in studies that addressed KQ2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies addressed only KQ1, 6 , 7 , 10 , 21 , 22 , 27 4 addressed only KQ2, 28 , 29 , 30 , 31 and 5 studies addressed both KQs. 5 , 8 , 9 , 11 , 32 Study and patient characteristics of included studies are reported in the Table . There were 8007 patients in studies that addressed KQ1 and 3243 patients in studies that addressed KQ2.…”
Section: Resultsmentioning
confidence: 99%
“…We used the Knapp and Hartung method to adjust the SEs of the estimated coefficients. 23 , 24 One study contained censored data, 9 and censored patients were removed so that only patients with complete follow-up information were included. Robustness of the findings was assessed through influence and sensitivity analyses as detailed in the Results section.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations